DIMENSIONS OF MIDWIVES' SATISFACTION WITH THE MANUAL BOOK OF THE MATERNAL EMERGENCY REFERRAL SYSTEM IN THE ISLANDS (SIRUTAN) - Darwitri, Darwitri; Melly Damayanti; Ristina Rosauli Harianja; Metasari Sihaloho; Nurul Aini Suria Saputri; Tiyara Safitri (Bajang Institute, 2025)
This study aims to evaluate the satisfaction of midwives with the manual book of the Maternal Emergency Referral System in the Islands (Si-RUTAN) in supporting effective maternal emergency care in remote island regions. A cross-sectional descriptive study was conducted involving 30 midwives from public health centers across the Riau Islands Province in 2024. In addition, the manual was evaluated by an obstetrics and gynecology expert (SpOG) using Nielsen's heuristic usability principles. The data were analyzed using univariate descriptive statistics. Most midwives reported high satisfaction with the manual: 83.3% were